Managerial Ability, Earnings Management and Fair Value Accounting: Does Debt Policy Matter? - Cahyani, Ana Dwi; Firmansyah, Amrie (Jurnal Dinamika Akuntansi dan Bisnis, 2023)
This study examines the impact of managerial ability and earnings management on fair value accounting. It also examines debt policy as a moderator in the relationship between the tested variables. The data was a panel data collected from infrastructure, utility, and transportation companies listed on the Indonesia Stock Exchange. The samples are 20 companies selected using purposive sampling and period of study is 5 years (2016 to 2020). Using multiple linear regression analysis, this study found that managerial ability is positively associated with fair value accounting, while earnings management is not associated with fair value accounting. Furthermore, debt policy strengthens the positive effect of managerial ability on fair value accounting, but it does not moderate the relationship between earnings management and fair value accounting. This study is an extension of previous research by placing a more complex role of managers in examining fair value accounting, which contributes to the financial accounting literature.